Confining FeS in graphitized carbon with void space for high and stable electrochemical storage performance of Na+ and K+. (14th April 2020) - Wang, Rong; Cao, Liyun; Li, Jiayin; Huang, Jianfeng; Xu, Zhanwei; Guo, Penghui; Chen, Shaoyi
Summary: Ferrous sulfides have high theoretical capacity in the electrochemical storage of Na‐ion and K‐ion, but its obvious volume change during the storage process greatly affects its cycling performance at high current density. In this regard, we construct a unique composites structure of Nitrogen‐doped carbon shell coated FeS nanoparticle with inner void spaces. As an anode in Na‐ion and K‐ion batteries, this structure could provide excellent cycling performance at high rate of charge/discharge process (560 mAh/g at 0.5 A/g for 300 cycles in Na‐ion battery and 322 mAh/g at 1 A/g for 300 cycles in K‐ion battery). Further research finds the inner void space could not only provide buffer space for the volume change of FeS nanoparticles, but also maintain a stable outer carbon shell during the electrochemical process. These behaviors greatly promote the reversibility of FeS at high rate charge transfer process. Consequently, the construction of inner void space in graphitized carbon shell in this work could be considered as an important reference for the promotion of electrochemical storage in other transitional metal compound system. Abstract : FeS nanoparticles are confined in graphitized carbon shell via a facile pyrolysis‐sulfidation strategy. Utilizing etching treatment could successfully create void spaces for the confined FeS nanoparticles in carbon shell. When the FeS nanoparticles are confined void space in carbon shell, they could provide greatly enhanced electrochemical storage performance of Na + and K + .